The Division and Structure of “David’s Compositions” (11Q5) - Biegas, Marcin Jan (The Biblical Annals, 2023)
The 11Q5 scroll is the longest and best-preserved manuscript containing psalms. In col. XXVII, it includes a hitherto unknown work, bearing the title “David’s Compositions.” Beginning with the critical edition, through various works devoted to the analysis of the composition from col. XXVII (2–11), the text is considered the only instance of prose in 11Q5. The main aim of the paper is to analyse the text of David’s Compositions in order to determine its literary form and structure. The paper is divided into several sections. The first section presents the Hebrew text with an English translation and a few remarks focused on the physical description of the text of David’s Compositions. The next one is a brief analysis of the internal context of the end of the Great Psalms Scroll, where the analysed text of David’s Compositions can be found. Finally, and most importantly, the Compositions were divided into verses and their literary form and structure was determined.